-1,53:(5|5/28-1|8/9*1,25+1|16/63
\(-1,53:\left(5\dfrac{5}{28}-1\dfrac{8}{9}.1,25+1\dfrac{16}{63}\right)\)
\(-1,53:\left(5\dfrac{5}{28}-1\dfrac{8}{9}\cdot1.25+1\dfrac{16}{63}\right)\)
\(=-\dfrac{153}{100}:\left(\dfrac{145}{28}-\dfrac{17}{9}\cdot\dfrac{5}{4}+\dfrac{79}{63}\right)\)
\(=-\dfrac{153}{100}:\left(\dfrac{145}{28}-\dfrac{85}{36}+\dfrac{79}{63}\right)\)
\(=-\dfrac{153}{100}:\dfrac{1395-595+316}{252}\)
\(=-\dfrac{153}{100}\cdot\dfrac{252}{1116}=\dfrac{-153}{100}\cdot\dfrac{7}{31}=\dfrac{-1071}{3100}\)
I = \(-1,53:\left(5\dfrac{5}{28}-1\dfrac{8}{9}.1,25+1\dfrac{16}{63}\right)\)
tính: -1,53 : \(\left(5\dfrac{5}{28}-1\dfrac{8}{9}.1,25+1\dfrac{16}{63}\right)\)
\(-1,53:\left(5\dfrac{5}{28}-1\dfrac{8}{9}.1,25+1\dfrac{16}{63}\right)\)
\(=-1,53:\left(5\dfrac{5}{28}-\dfrac{17}{9}.\dfrac{5}{4}+1\dfrac{16}{63}\right)\)
\(=-1,53:\left(5\dfrac{5}{28}-\dfrac{17.5}{9.4}+1\dfrac{16}{63}\right)\)
\(=-1,53:\left(5\dfrac{5}{28}-\dfrac{85}{36}+1\dfrac{16}{63}\right)\)
\(=-1,53:\left(\dfrac{145}{28}-\dfrac{85}{36}+\dfrac{79}{63}\right)\)
\(=-1,53:\left(\dfrac{1305}{252}-\dfrac{595}{252}+\dfrac{316}{252}\right)\)
\(=-1,53:\dfrac{1305-595+316}{252}\)
\(=-1,53:\dfrac{1026}{252}\)
\(=\dfrac{-153}{100}:\dfrac{57}{14}\)
\(=\dfrac{-153}{100}.\dfrac{14}{57}\)
\(=\dfrac{-153.14}{100.57}\)
\(=\dfrac{-2142}{5700}\)
\(=\dfrac{-357}{950}\)
Tính
A = -1,53 : ( \(5\frac{5}{28}\)- \(1\frac{8}{9}\).1,25 + \(1\frac{16}{63}\))
Giúp tớ với
A =15/34 + 7/21 + 9/34 - 1 15/17 + 2/3
B = 16 2/7 : ( - 3/5 ) - 28 2/7 : ( - 3/5 )
C = 25.(- 1/3) 3 + 1/5 - 2.( - 1/2 )2 -1/2
D = ( - 2 )3 . ( 3/4 - 0,25 ) : ( 2 1/4 - 1 1/6 )
F = ( - 3/2 )2 + |- 5/6 | - 1 1/2 : 6
I = - 1,53 : ( 5 5/28 - 1 8/9 .1,25 + 1 16/63 )
tính giá trị biểu thức
-5,13/(5 5/28-1 8/9*1,25+1 16/63)
tính giá trị của biểu thức:
\(A=-5,13:\left(5\dfrac{5}{28}-1\dfrac{8}{9}.1,25+1\dfrac{16}{63}\right)\)
\(A=-5,13:\left(5\dfrac{5}{28}-1\dfrac{8}{9}.1,25+1\dfrac{16}{63}\right)\)
\(=-5,13:\left(5\dfrac{5}{28}-2\dfrac{13}{36}+1\dfrac{16}{63}\right)\)
\(=5,13:\left[\left(5-2+1\right)+\left(\dfrac{5}{28}-\dfrac{13}{36}+\dfrac{16}{63}\right)\right]\)
\(=5,13:\left(4+\dfrac{1}{14}\right)\)
\(=1,26\)
`A=-5,13:(5 5/28-1 8/9 .1,25+1 16/63)`
`A=-513/100:(145/28-17/9 .5/4+79/63)`
`A=-513/100:(145/28-85/36+79/63)`
`A=-513/100:(355/126+79/63)`
`A=-513/100:57/14`
`A=-63/50`
\(A=-5,13:\left(5\dfrac{5}{28}-1\dfrac{8}{9}.1,25+1\dfrac{16}{63}\right)\)
\(A=-5,13:\left[\left(5-2+1\right)+\left(\dfrac{5}{28}-\dfrac{18}{36}+\dfrac{16}{63}\right)\right]\)
\(A=-5,13:\left(4+\dfrac{1}{14}\right)\)
\(A=-5,13:\left(\dfrac{56}{14}+\dfrac{1}{14}\right)\)
\(A=-5,13:\dfrac{57}{14}\)
\(A=\dfrac{-513}{100}:\dfrac{57}{14}\)
\(A=\dfrac{-513}{100}\times\dfrac{14}{57}\)
\(A=\dfrac{-63}{50}\)
tính giá trị của biểu thức
A=-5,13:(\(5\dfrac{5}{28}-1\dfrac{8}{9}.1,25+1\dfrac{16}{63}\)
A= -5,13: (\(5\dfrac{5}{28}\)-\(1\dfrac{8}{9}\).1,25+\(1\dfrac{16}{63}\))
A=-5,13:(\(\dfrac{145}{28}\)-\(\dfrac{17}{9}\). 1,25+\(\dfrac{79}{63}\))
A= -5,13:(\(\dfrac{145}{28}\)-\(\dfrac{85}{36}\)+ \(\dfrac{79}{63}\))
A= -5,13:\(\dfrac{57}{14}\)
A= -\(\dfrac{63}{50}\)
\(A=-5,13:\left(5\dfrac{5}{28}-1\dfrac{8}{9}.1,25+1\dfrac{16}{63}\right)\)
\(A=-5,13:\left(5\dfrac{5}{28}-\dfrac{85}{36}+1\dfrac{16}{63}\right)\)
\(A=-5,13:\dfrac{57}{14}\)
\(A=\dfrac{-63}{50}\)
\(A=-5,13:\left(\dfrac{5\cdot28+5}{28}-\dfrac{1\cdot9+8}{9}\cdot1,25+\dfrac{1\cdot63+16}{63}\right)\)
\(A=-5,13:\left(\dfrac{145}{28}-\dfrac{85}{36}+\dfrac{79}{63}\right)\)
\(A=-5,13:\left(\dfrac{57}{14}\right)=-5,13\cdot\dfrac{14}{57}=-\dfrac{63}{50}\)
CHÚC BẠN HỌC TỐT !!!
Bài 1: Tính giá trị biểu thức:
A = \(-1,53:\left(5\frac{5}{28}-1\frac{8}{9}.1,25+1\frac{16}{83}\right)\)
B = \(\left(3\frac{1}{3}.1,9+9,5:4\frac{1}{3}\right):\left(\frac{62}{75}-\frac{4}{25}\right)\)